RELIABILITY BASED MAINTENANCE ANALYSIS OF THE MAIN ENGINE LUBRICATION SYSTEM OF THE KM-KELIMUTU SHIP - Yudo, Hartono; Dwi Putra Naya, Radityo Habil (TRAKSI, 2024)
The main engine on KM. Kelimutu operates with the help of KM. Kelimutu ship system itself. The exitences of  a system that can be considered very critical is lubrication system of the main engine. The lubrication system for the main engine of KM. Kelimutu itself has task of the supporting the smooth operation of the main engine by distributing good lubrication and in accordance with the main engine indicators. Failure of this lubrication system will have a negative impact on the main engine, therefore the purpose of this study is to analyze the KM. Kelimutu lubrication system with the reliability method. In this study, the reliability method used to analyze the lubrication system uses qualitative analysis and quantitative analysis. Qualitative analysis using Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). Meanwhile, for quantitative analysis by conducting a Monte Carlo simulation. The results of this study indicate that the most critical component in KM. Kelimutu lubrication system is a filter with an initial Risk Priority Number (RPNi) value of 592, and if the component have 2 pieces such as a filter, transfer pump, Lo pump, and also a Lo separator have failed.  The results of the simulation show Availability is 0,96 and MTTF (Mean Time to Failure) is 697,76082.